Preparation method of polyatom-doped silicon-carbon composite negative electrode material

By using the preparation method of multi-atom doped silicon-carbon composite negative electrode material in lithium-ion battery materials, the problem of poor doping uniformity is solved, the material's high conductivity, electrochemical activity and cycle stability is achieved, and the performance of lithium-ion battery is improved.

CN119797361AActive Publication Date: 2025-04-11SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411780473.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Poor doping uniformity in existing lithium-ion battery materials leads to poor performance.

Method used

A method for preparing a polyatom doped silicon-carbon composite negative electrode material is adopted. By carbonizing the biomass carbon-based precursor and copper metal dopant in a tube furnace, porous carbon is formed, and then reducing reaction is carried out in a fluidized bed reactor. Then, multiple reactions are carried out in a vacuum furnace. Finally, acetylene/heteroatom mixed gas is heated in the rotary furnace to obtain a polyatom doped silicon-carbon composite negative electrode material.

Benefits of technology

Through this method, the preparation of a polyatom doped silicon-carbon composite negative electrode material with extremely high doping uniformity is achieved, and the conductivity, electrochemical activity and cycle stability of the material are improved, thereby improving the performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797361A_ABST
    Figure CN119797361A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a multi-atom doped silicon-carbon composite negative electrode material, which comprises the following steps: transferring a biomass carbon-based precursor and a copper metal dopant into a tubular furnace, and carrying out carbonization reaction to obtain porous carbon; transferring the porous carbon to a fluidized bed reactor, and introducing an organic carbon source / hydrogen mixed gas for reduction reaction to obtain copper-doped porous carbon; transferring the copper-doped porous carbon into a vacuum furnace, sequentially introducing nitrogen source gas, lithium source gas and silicon source / carbon source mixed gas, and carrying out segmented multiple reactions to obtain a silicon-carbon precursor; and transferring the silicon-carbon precursor into a rotary furnace, heating, introducing acetylene / heteroatom mixed gas, and cooling to obtain the polyatom doped silicon-carbon composite negative electrode material. The porous structure provides a large amount of energy storage space, and the introduction of copper doping further improves the electronic conductivity and ionic conductivity, and enhances the electrochemical activity, cycling stability and other properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery material production, and in particular relates to a method for preparing a multi-atom doped silicon-carbon composite negative electrode material. Background Art

[0002] Due to the high capacity characteristics of silicon, compared with traditional graphite negative electrodes, multi-atom doped silicon-carbon composite negative electrode materials can provide higher energy density and improve the total capacity of the battery. Through the structural design of porous carbon, multi-atom doped silicon-carbon composite negative electrode materials can inhibit the negative effects of silicon expansion and contraction to a certain extent and extend the service life of the battery. Although silicon itself has poor conductivity, the electronic conductive network of porous carbon can improve the overall conductivity of the composite material and enhance its power performance during rapid charging and discharging.

[0003] The current new silicon carbon is mainly composed of porous carbon and nano-silicon deposited in the pores. It has poor electronic conductivity, which causes the power performance of the material to deviate. Although some researchers have improved the electronic conductivity of the material by doping metal or non-metallic elements in porous carbon, the volatilization of the doping elements during the high-temperature carbonization process causes the doping effect to be unobvious. The reason is that the material doping elements are prepared in steps under different temperatures and other conditions, resulting in poor doping uniformity of the material and poor binding force between the doping elements and the main elements, which has a greater impact on the power of lithium-ion battery materials and leads to poor performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a multi-atom doped silicon-carbon composite negative electrode material, aiming to solve the problem of poor doping uniformity and poor performance of lithium-ion battery materials.

[0005] To solve the above technical problems, the present invention is implemented as follows: a method for preparing a multi-atom doped silicon-carbon composite negative electrode material, the steps comprising: S1. Transferring a biomass carbon-based precursor and a copper metal dopant to a tube furnace, and performing a carbonization reaction to obtain porous carbon, wherein the mass ratio of the biomass carbon-based precursor to the copper metal dopant is 500:10-30, the biomass carbon-based precursor comprises at least one of coconut shell, rice shell, fruit shell, and sawdust, and the copper metal dopant comprises at least one of copper chloride, copper nitrate, and copper sulfate; S2, transferring the porous carbon to a fluidized bed reactor, introducing an organic carbon source / hydrogen mixed gas to carry out a reduction reaction, and obtaining copper-doped porous carbon; S3, transferring the copper-doped porous carbon to a vacuum furnace, introducing nitrogen source gas, lithium source gas, and silicon source / carbon source mixed gas in sequence for multiple staged reactions to obtain a silicon-carbon precursor; S4, transferring the silicon-carbon precursor to a rotary furnace, heating it and introducing acetylene / heteroatom mixed gas, and obtaining a multi-atom doped silicon-carbon composite negative electrode material after cooling.

[0006] In some embodiments of the present invention, step S1 comprises: S1.1, mixing the bio-to-carbon-based precursor and the copper metal dopant uniformly and transferring them to a tube furnace for first heating, wherein the first heating temperature is 700-900° C. and the first heating time is 1-6 hours; S1.2. After the first heating is completed, a second heating is performed and an activated gas is introduced to obtain porous carbon, wherein the temperature of the second heating is 1000-1200°C, the time of the second heating is 1-3h, the activated gas includes at least one of water vapor, carbon dioxide, and hydrogen, and the flow rate of the activated gas is 100-500ml / min.

[0007] In some embodiments of the present invention, in step S2, the pressure condition of the reduction reaction is 0.1-0.5 MPa, the temperature of the reduction reaction is 700-900° C., and the time of the reduction reaction is 1-10 h.

[0008] In some embodiments of the present invention, step S3 includes: S3.1, transferring the copper-doped porous carbon to a vacuum furnace, adjusting the gas pressure to 0.1-0.5 MPa, performing the first stage heating and introducing a nitrogen source gas, wherein the nitrogen source gas includes at least one of ammonia, nitrogen, and nitric oxide, the flow rate of the nitrogen source gas is 10-50 SCCM, the introduction time of the nitrogen source gas is 0.5-3 h, and the temperature of the first stage heating is 600-900 ° C; S3.2, after stopping the introduction of the nitrogen source gas, the second stage of heating and the introduction of the lithium source gas, wherein the temperature of the second stage heating is 1000-1400°C, the lithium source gas includes at least one of lithium hydride and lithium vinyl, the flow rate of the lithium source gas is 100-500 SCCM, and the introduction time of the lithium source gas is 0.5-3h; S3.3. After stopping the introduction of the lithium source gas, the third stage of heating is carried out and a silicon source / carbon source mixed gas is introduced to obtain a silicon-carbon precursor, wherein the temperature of the third stage heating is 400-600°C, the silicon source gas in the silicon source / carbon source mixed gas includes at least one of monosilane, disilane, dichlorosilane, and trichlorosilane, the carbon source gas in the silicon source / carbon source mixed gas includes at least one of ethylene, acetylene, propane, cyclohexane, methane, and benzene, the flow rate of the silicon source / carbon source mixed gas is 100-500 SCCM, and the introduction time of the silicon source / carbon source mixed gas is 1-10 hours.

[0009] In some embodiments of the present invention, in step S3.3, the volume ratio of the silicon source gas to the carbon source gas in the silicon source / carbon source mixed gas is 10:1-5.

[0010] In some embodiments of the present invention, in step S4, the heteroatom gas in the acetylene / heteroatom mixed gas includes at least one of hydrogen sulfide, ammonia, phosphine, and tetrahydrogen, the flow rate of the acetylene / heteroatom mixed gas is 100~500SCM, and the introduction time of the acetylene / heteroatom mixed gas is 1~10h.

[0011] In some embodiments of the present invention, step S4 includes: S4.1, transferring the silicon-carbon precursor to a rotary furnace, first heating it to a first temperature and introducing acetylene / heteroatom mixed gas, wherein the first temperature is 200-300° C.; S4.2. Maintain the preset heating rate to heat up to the second temperature, and at the same time adjust the rotation speed of the rotary kiln and the flow rate of the acetylene / heteroatom mixed gas. After the acetylene / heteroatom mixed gas is introduced, it is cooled to obtain a multi-atom doped silicon-carbon composite negative electrode material, wherein the rotation speed is positively correlated with the flow rate of the acetylene / heteroatom mixed gas, wherein the preset heating rate is 5~80℃ / h, and the second temperature is 400~500℃.

[0012] In some embodiments of the present invention, the multi-atom doped silicon-carbon composite negative electrode material is applied to a lithium-ion battery.

[0013] Compared with the prior art, the preparation method of the multi-atom doped silicon-carbon composite negative electrode material in the present invention has the following beneficial effects: The rich organic components in the biomass carbon-based precursor undergo a high-temperature carbonization reaction in a tube furnace to form a porous carbon structure. This structure has a large specific surface area and good pore distribution, which provides a highly uniform substrate for subsequent doping. The copper metal dopant combines with the carbon structure of the biomass carbon-based precursor through a chemical reaction to achieve uniform doping during the carbonization process and form a copper-doped porous carbon material. This copper-doped material can not only improve the conductivity of porous carbon due to its extremely uniform doping effect, but also provide more catalytic active sites in subsequent reactions or applications.

[0014] Due to the structural characteristics of porous carbon and the promotion of copper doping, the porous carbon material can improve its performance in electrochemical devices such as lithium-ion batteries and capacitors when used as negative electrode materials. The porous structure provides a large amount of energy storage space, and the introduction of copper doping further improves the electronic conductivity and ionic conductivity, enhances the electrochemical activity and cycle stability of the material, and thus improves the performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic flow chart of a method for preparing a composite substrate for producing a semiconductor device in one embodiment of the present invention; Figure 2 This is a SEM image of the multi-atom doped silicon-carbon composite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0017] Embodiment 1: Embodiment 1 of the present invention provides a method for preparing a multi-atom doped silicon-carbon composite negative electrode material, the steps comprising: S1. Transferring the biomass carbon-based precursor and the copper metal dopant to a tubular furnace, and performing a carbonization reaction to obtain porous carbon, wherein the mass ratio of the biomass carbon-based precursor and the copper metal dopant is 500:20, the biomass carbon-based precursor is 500g of coconut shell, and the copper metal dopant is 20g of copper chloride powder.

[0018] By mixing the biomass carbon-based precursor with the copper metal dopant in a certain mass ratio and transferring it to a tube furnace for carbonization reaction, the biomass carbon-based precursor can be effectively converted into a carbon material with a porous structure. The copper metal dopant participates in the carbonization reaction during the reaction and promotes the structural stability of the carbon, thereby obtaining a porous carbon material with excellent specific surface area and good pore structure.

[0019] The rich organic components in the biomass carbon-based precursor undergo a high-temperature carbonization reaction in a tube furnace to form a porous carbon structure. This structure has a large specific surface area and good pore distribution, which provides an ideal substrate for subsequent doping and other functional reactions. The formation of a porous structure also makes the carbon material have stronger adsorption properties and higher reactivity.

[0020] The copper metal dopant can be evenly dispersed in the carbon material during the reaction. The copper ions combine with the carbon structure of the biomass carbon-based precursor through chemical reactions, and are doped during the carbonization process to form a copper-doped porous carbon material. This copper-doped material can not only improve the conductivity of the porous carbon, but also provide more catalytic active sites in subsequent reactions or applications.

[0021] Due to the structural characteristics of porous carbon and the promotion of copper doping, the porous carbon material can improve its performance in electrochemical devices such as lithium-ion batteries and capacitors when used as anode materials. The porous structure provides a large amount of energy storage space, and the introduction of copper doping further improves the electronic conductivity and ionic conductivity, thereby enhancing the electrochemical activity and cycle stability of the material.

[0022] Biomass carbon-based precursors are widely available and easy to obtain, and are a renewable green resource. Through this technical path, we can not only reduce our dependence on traditional mineral resources, but also make use of discarded agricultural byproducts or plant raw materials for resource utilization, which meets the needs of green, environmentally friendly and sustainable development.

[0023] The mass ratio of the biomass carbon-based precursor and the copper metal dopant, reaction conditions and other parameters in the preparation method can be flexibly adjusted to adjust the pore structure, conductivity, doping degree and other characteristics of the final product. This adjustability enables the technology to prepare porous carbon materials with optimized performance according to specific application requirements.

[0024] Step S1 includes: S1.1, mixing the bio-to-carbon-based precursor and the copper metal dopant evenly and transferring them to a tube furnace for first heating, wherein the first heating temperature is 800° C. and the first heating time is 3 hours.

[0025] The process can effectively convert the biomass raw material into a preliminary carbonized material by mixing the biomass carbon-based precursor and the copper metal dopant uniformly and transferring them to a tube furnace for the first heating. This temperature range is sufficient to induce the decomposition, dehydration and degassing of the organic components in the biomass carbon-based precursor, thus laying the foundation for subsequent high-temperature treatment and activation.

[0026] The copper metal dopant begins to react with the carbon-based precursor during the first heating process, and some copper ions may penetrate into the carbon material, providing the necessary conditions for subsequent doping reactions and the formation of a porous structure. This process helps lay the foundation for the material's performance in the initial carbonization stage.

[0027] The control of temperature and time ensures the controllability of the reaction during the first heating process, avoids uneven carbon structure caused by too fast carbonization reaction, and avoids excessive reduction of copper metal dopants, ensuring the stability of the doping effect.

[0028] S1.2. After the first heating is completed, a second heating is performed and an activated gas is introduced to obtain porous carbon, wherein the second heating temperature is 1100°C, the second heating time is 2h, the activated gas is water vapor, and the flow rate of the activated gas is 300ml / min.

[0029] This second heating process further activates the porous carbon material formed during the carbonization process. The activated gas reacts with the carbon material, promoting oxidation of its surface, removing unnecessary impurities and generating more pores in the carbon structure. This process significantly increases the specific surface area and porosity of the material, giving it higher energy storage, adsorption and reactivity.

[0030] During the second heating process, the effect of the copper metal dopant is further enhanced. The copper metal ions may react with the activation gas or be further fixed in the pores of the carbon-based material through heat treatment, thereby enhancing the electrochemical, conductive and catalytic properties of the material.

[0031] Through the second heating and activation, not only more micropores and mesopores are formed on the surface of the material, but also its specific surface area in applications such as batteries and capacitors is increased, thereby improving the electrochemical performance of the material. The activated gas can remove oxides that may be produced during the carbonization process, improve the purity and stability of the material, and provide a more ideal substrate for subsequent lithium-ion battery negative electrode materials.

[0032] The activation process of activated gas can regulate the pore structure, form more micropores and mesopores, optimize the pore size distribution of carbon materials, and make them have better adsorption performance and chemical stability. This porous structure not only helps to improve the electrochemical performance, but also improves the surface reactivity of the material, thereby enhancing the subsequent doping reaction and application effect.

[0033] During the second heating process, the uniformity of the activation process can be effectively guaranteed, oxidation or uneven activation caused by excessive gas can be avoided, and the efficiency of the activation reaction can be guaranteed. Reasonable flow and temperature control can help obtain porous carbon materials with high specific surface area and good porosity.

[0034] S2. Transfer the porous carbon to a fluidized bed reactor, introduce an organic carbon source / hydrogen mixed gas for reduction reaction, and obtain copper-doped porous carbon. The pressure condition of the reduction reaction is 0.3Mpa, the temperature of the reduction reaction is 800°C, and the time of the reduction reaction is 5h. This process not only improves the electrical conductivity of the carbon material, but also enhances its electrochemical activity and catalytic performance. The organic carbon source gas in the organic carbon source / hydrogen mixed gas includes at least one of methane, ethylene, ethane, hydrogen, carbon monoxide, methanol, and benzene.

[0035] Under the combined action of hydrogen and organic carbon sources, copper metal dopants can be smoothly reduced and fixed in the pores of carbon materials. Copper metal dopants have good catalytic properties and can provide catalytic sites in subsequent reactions or applications, promoting efficient charging and discharging reactions of devices such as batteries or capacitors. The surface structure of copper-doped porous carbon materials changes significantly after the reduction reaction, with more active sites, which can significantly improve their electrochemical performance in energy storage devices such as lithium-ion batteries or supercapacitors. Copper doping not only improves conductivity, but may also enhance the battery's cycle stability and high-rate performance.

[0036] The reduction reaction conditions help to further optimize the pore structure of porous carbon materials, increase their specific surface area and porosity, and thus improve the adsorption performance, energy storage capacity, and reactivity of the materials. Through the action of hydrogen reduction and organic carbon sources, more active sites may appear on the surface of carbon materials, further enhancing their stability and efficiency in electrochemical reactions. By precisely controlling the flow and ratio of hydrogen and organic carbon sources, the effect of the reduction reaction can be optimized, ensuring the complete reduction of copper metal and maximizing the conductivity and chemical stability of porous carbon materials. The control of atmosphere conditions and flow can avoid excessive or insufficient reduction of copper metal, and can also ensure the efficiency and uniformity of the reaction, thereby improving the performance of the final material.

[0037] S3. The copper-doped porous carbon is transferred to a vacuum furnace, and nitrogen source gas, lithium source gas, and silicon source / carbon source mixed gas are introduced in sequence to perform multiple staged reactions to obtain a silicon-carbon precursor.

[0038] The staged multiple reactions introduce different gas sources (nitrogen source, lithium source, silicon source / carbon source) in different stages, and can finely control the reaction conditions, such as temperature, gas flow rate and reaction time, at each reaction stage. This ensures that each element is fully doped and evenly distributed, thereby improving the uniformity, stability and performance of the silicon-carbon precursor. Through staged reactions, the interaction between each reaction gas and the precursor material can be effectively controlled to avoid byproducts or uneven doping problems caused by excessive reactions.

[0039] Specifically, step S3 includes: S3.1, transferring the copper-doped porous carbon to a vacuum furnace, adjusting the gas pressure to 0.3 MPa, performing the first stage heating and introducing the nitrogen source gas, wherein the nitrogen source gas is ammonia, the flow rate of the nitrogen source gas is 30 SCCM, the introduction time of the nitrogen source gas is 150 min, and the temperature of the first stage heating is 700°C.

[0040] During the first stage of heating, the introduction of nitrogen source gas helps to form a stable nitrogen atmosphere during this heating stage, preventing oxidation and providing a suitable environment for subsequent doping reactions. The nitrogen source gas can also react with the surface of the porous carbon substrate to generate nitrides, improving the conductivity, chemical stability and mechanical strength of the material.

[0041] The temperature at this stage is conducive to the initial development of the copper-doped porous carbon surface reaction, and also provides pretreatment conditions for the subsequent lithium source and silicon source gas reactions. The flow rate setting and introduction time of the nitrogen source gas can ensure sufficient reaction, avoid side reactions caused by excessive gas, and ensure the uniformity of doping.

[0042] S3.2. After stopping the introduction of the nitrogen source gas, the second stage of heating is carried out and the lithium source gas is introduced, wherein the temperature of the second stage heating is 1200° C., the lithium source gas is lithium hydride, the flow rate of the lithium source gas is 300 SCCM, and the introduction time of the lithium source gas is 150 min.

[0043] The temperature of the second stage heating is sufficient to promote the effective incorporation and reaction of the lithium source gas. The lithium source gas provides lithium elements, which can react with porous carbon and silicon sources to generate lithium silicon alloys with high electrochemical performance. The introduction of lithium significantly improves the conductivity and stability of multi-atom doped silicon-carbon composite negative electrode materials, and improves their performance in lithium-ion batteries, especially the inhibition of capacity attenuation and volume expansion.

[0044] The flow rate and introduction time of the reaction gas are set to ensure that the lithium source gas fully reacts with the porous carbon, avoiding excess or deficiency of the lithium source gas, thereby ensuring the integrity and uniformity of the lithium doping reaction.

[0045] S3.3, after stopping the introduction of lithium source gas, the third stage of heating is carried out and silicon source / carbon source mixed gas is introduced to obtain a silicon-carbon precursor, wherein the temperature of the third stage of heating is 500°C, the silicon source gas in the silicon source / carbon source mixed gas is monosilane, the carbon source gas in the silicon source / carbon source mixed gas is ethylene, the flow rate of the silicon source / carbon source mixed gas is 300 SCCM, and the introduction time of the silicon source / carbon source mixed gas is 150 min. The volume ratio, monosilane gas:ethylene gas = 10:3.

[0046] The lower temperature setting in the third stage makes the reaction of the silicon source and carbon source mixed gas milder, which helps to form the structure of the silicon-carbon composite precursor. At this temperature, monosilane gas and ethylene gas react to form a uniformly distributed multi-atom doped silicon-carbon composite negative electrode material. The temperature in this stage helps to balance the reaction speed and material stability, avoiding overreaction or side reactions under high temperature conditions.

[0047] Adjusting the volume ratio of silicon source gas and carbon source gas is beneficial to controlling the ratio of silicon to carbon in the final product, ensuring that the final multi-atom doped silicon-carbon composite negative electrode material has appropriate conductivity and stability. The introduction of silicon source gas ensures sufficient doping of silicon elements, while carbon source gas helps form stable carbon-based materials.

[0048] The flow rate and introduction time of the silicon source / carbon source mixed gas are set to ensure the adequacy of the reaction time and to ensure the effective doping and uniform distribution of silicon and carbon elements.

[0049] S4. Transfer the silicon-carbon precursor to a rotary kiln, heat it and introduce acetylene / heteroatom mixed gas. After the reaction is completed, a multi-atom doped silicon-carbon composite negative electrode material is obtained. The heteroatom gas in the acetylene / heteroatom mixed gas is hydrogen sulfide, the flow rate of the acetylene / heteroatom mixed gas is 100~500SCM, and the introduction time of the acetylene / heteroatom mixed gas is 150min. The volume ratio, acetylene: hydrogen sulfide = 10:3.

[0050] The use of a rotary kiln can ensure that the silicon-carbon precursor reacts under uniform heating conditions. The rotation of the rotary kiln can ensure that the precursor material is heated evenly, preventing local overheating or incomplete reaction. In addition, the rotary kiln can achieve full contact between gas and solid materials at a higher temperature and optimize the reaction process. When heated in a rotary kiln, the increase in temperature will promote the further combination of silicon and other doping elements in the multi-atom doped silicon-carbon composite negative electrode material, enhancing the structural stability and electrochemical performance of the material.

[0051] S4.1, transferring the silicon-carbon precursor to a rotary furnace, first heating it to a first temperature and introducing acetylene / heteroatom mixed gas, wherein the first temperature is 300° C.; S4.2. Maintain the preset heating rate to heat up to the second temperature, and at the same time adjust the rotation speed of the rotary kiln and the flow rate of the acetylene / heteroatom mixed gas. After the acetylene / heteroatom mixed gas is introduced, it is cooled to obtain a multi-atom doped silicon-carbon composite negative electrode material, wherein the rotation speed is positively correlated with the flow rate of the acetylene / heteroatom mixed gas, wherein the preset heating rate is 60°C / h, and the second temperature is 450°C.

[0052] The heating process is controlled by a preset heating rate to ensure that the reaction materials receive uniform and stable heat input during the heating process, avoiding incomplete local reactions or uneven reactants caused by excessive temperature fluctuations.

[0053] The rotation speed is positively correlated with the flow rate of acetylene / heteroatom mixed gas, which can optimize the residence time and flow trajectory of the material in the furnace, thereby ensuring full contact between the material and the reaction gas and enhancing the uniformity and consistency of the reaction. The appropriate rotation speed can avoid the aggregation or agglomeration of the material in the furnace, thereby improving the dispersion and reaction efficiency of the reaction materials. The specific relationship is current gas flow = k·(current rotation speed / maximum rotation speed)·maximum gas flow, k is a proportional relationship constant, k can be 0.5~1, and the rotation speed of the rotary kiln is 50~200 rpm. By adjusting the flow rate of acetylene / heteroatom mixed gas and the rotation speed of the furnace body at the same time during the reaction process, the flow of gas and the movement trajectory of the material are more matched. This coordination helps to maintain the stability of the reaction atmosphere, avoid uneven distribution of gas, and improve the reaction efficiency of the material.

[0054] The acetylene / heteroatom mixed gas reacts with the silicon-carbon precursor during the heating process, which helps to uniformly dope the heteroatoms into the multi-atom doped silicon-carbon composite negative electrode material. By precisely adjusting the rotation speed and gas flow rate, it is possible to ensure that the heteroatoms are distributed more evenly in the material, avoiding local concentrations that are too high or too low, thereby obtaining a multi-atom doped silicon-carbon composite negative electrode material with better performance. By maintaining a preset heating rate, the reaction process is more controllable, avoiding uneven gas flow or incomplete material reaction caused by rapid temperature changes. After the acetylene / heteroatom gas is introduced, timely cooling helps maintain the structural characteristics of the material and stop the reaction, preventing overreaction or the formation of unstable compounds.

[0055] Embodiment 2: Embodiment 2 of the present invention provides a method for preparing a multi-atom doped silicon-carbon composite negative electrode material, the steps comprising: S1. Transferring the biomass carbon-based precursor and the copper metal dopant to a tubular furnace, and performing a carbonization reaction to obtain porous carbon, wherein the mass ratio of the biomass carbon-based precursor and the copper metal dopant is 500:10, the biomass carbon-based precursor is 500g of coconut shell, and the copper metal dopant is 10g of copper chloride powder.

[0056] Step S1 includes: S1.1, mixing the bio-to-carbon-based precursor and the copper metal dopant evenly and transferring them to a tube furnace for first heating, wherein the first heating temperature is 700° C. and the first heating time is 6 hours.

[0057] S1.2. After the first heating is completed, a second heating is performed and an activated gas is introduced to obtain porous carbon, wherein the second heating temperature is 1000°C, the second heating time is 3 hours, the activated gas is water vapor, and the flow rate of the activated gas is 100 ml / min.

[0058] S2, transferring the porous carbon to a fluidized bed reactor, introducing an organic carbon source / hydrogen mixed gas for reduction reaction, and obtaining copper-doped porous carbon. The organic carbon source gas in the organic carbon source / hydrogen mixed gas is ethylene, the volume ratio is ethylene: hydrogen = 10:3, the pressure condition of the reduction reaction is 0.3Mpa, the temperature of the reduction reaction is 700°C, and the time of the reduction reaction is 10h.

[0059] S3. The copper-doped porous carbon is transferred to a vacuum furnace, and nitrogen source gas, lithium source gas, and silicon source / carbon source mixed gas are introduced in sequence to perform multiple staged reactions to obtain a silicon-carbon precursor.

[0060] Specifically, step S3 includes: S3.1, transferring the copper-doped porous carbon to a vacuum furnace, adjusting the gas pressure to 0.1 MPa, performing the first stage heating and introducing the nitrogen source gas, wherein the nitrogen source gas is nitrogen, the flow rate of the nitrogen source gas is 10 SCCM, the introduction time of the nitrogen source gas is 300 min, and the temperature of the first stage heating is 600°C.

[0061] S3.2. After stopping the introduction of the nitrogen source gas, the second stage of heating is carried out and the lithium source gas is introduced, wherein the temperature of the second stage heating is 1000° C., the lithium source gas is lithium hydride, the flow rate of the lithium source gas is 100 SCCM, and the introduction time of the lithium source gas is 300 min.

[0062] S3.3, after stopping the introduction of lithium source gas, the third stage of heating is carried out and silicon source / carbon source mixed gas is introduced to obtain a silicon-carbon precursor, wherein the temperature of the third stage of heating is 400°C, the silicon source gas in the silicon source / carbon source mixed gas is disilane, the carbon source gas in the silicon source / carbon source mixed gas is acetylene, the flow rate of the silicon source / carbon source mixed gas is 100 SCCM, and the introduction time of the silicon source / carbon source mixed gas is 600 min. The volume ratio, disilane gas: acetylene gas = 10:1.

[0063] S4. Transfer the silicon-carbon precursor to a rotary kiln, heat it and introduce acetylene / heteroatom mixed gas, and obtain a multi-atom doped silicon-carbon composite negative electrode material after the reaction is completed. The heteroatom gas in the acetylene / heteroatom mixed gas is ammonia, the flow rate of the acetylene / heteroatom mixed gas is 100SCM, and the introduction time of the acetylene / heteroatom mixed gas is 600min. The volume ratio, acetylene: ammonia = 10:1, the heating temperature of the rotary kiln is 400℃.

[0064] Embodiment 3: Embodiment 3 of the present invention provides a method for preparing a multi-atom doped silicon-carbon composite negative electrode material, the steps comprising: S1. Transferring the biomass carbon-based precursor and the copper metal dopant to a tubular furnace, and performing a carbonization reaction to obtain porous carbon, wherein the mass ratio of the biomass carbon-based precursor and the copper metal dopant is 500:30, the biomass carbon-based precursor is 500g of coconut shell, and the copper metal dopant is 30g of copper chloride powder.

[0065] Step S1 includes: S1.1, mixing the bio-to-carbon-based precursor and the copper metal dopant evenly and transferring them to a tube furnace for first heating, wherein the first heating temperature is 900° C. and the first heating time is 1 hour.

[0066] S1.2. After the first heating is completed, a second heating is performed and an activated gas is introduced to obtain porous carbon, wherein the second heating temperature is 1200°C, the second heating time is 1 hour, the activated gas is water vapor, and the flow rate of the activated gas is 500 ml / min.

[0067] S2. The porous carbon is transferred to a fluidized bed reactor, and an organic carbon source / hydrogen mixed gas is introduced for reduction reaction to obtain copper-doped porous carbon. The organic carbon source gas in the organic carbon source / hydrogen mixed gas is methane, and the volume ratio is methane: hydrogen = 10:3. The pressure condition of the reduction reaction is 0.5 MPa, the temperature of the reduction reaction is 900°C, and the time of the reduction reaction is 1 hour.

[0068] S3. The copper-doped porous carbon is transferred to a vacuum furnace, and nitrogen source gas, lithium source gas, and silicon source / carbon source mixed gas are introduced in sequence to perform multiple staged reactions to obtain a silicon-carbon precursor.

[0069] Specifically, step S3 includes: S3.1, transferring the copper-doped porous carbon to a vacuum furnace, adjusting the gas pressure to 0.5 MPa, performing the first stage heating and introducing the nitrogen source gas, wherein the nitrogen source gas is nitrogen, the flow rate of the nitrogen source gas is 50 SCCM, the introduction time of the nitrogen source gas is 30 minutes, and the temperature of the first stage heating is 900°C.

[0070] S3.2. After stopping the introduction of the nitrogen source gas, the second stage of heating is carried out and the lithium source gas is introduced, wherein the temperature of the second stage heating is 1400° C., the lithium source gas is lithium hydride, the flow rate of the lithium source gas is 500 SCCM, and the introduction time of the lithium source gas is 60 min.

[0071] S3.3, after stopping the introduction of lithium source gas, the third stage of heating is carried out and silicon source / carbon source mixed gas is introduced to obtain a silicon-carbon precursor, wherein the temperature of the third stage of heating is 600°C, the silicon source gas in the silicon source / carbon source mixed gas is dichlorodihydrogen silicon, the carbon source gas in the silicon source / carbon source mixed gas is methane, the flow rate of the silicon source / carbon source mixed gas is 500 SCCM, and the introduction time of the silicon source / carbon source mixed gas is 60 minutes. The volume ratio, dichlorodihydrogen silicon gas: methane gas = 10:5.

[0072] S4. Transfer the silicon-carbon precursor to a rotary kiln, heat it and introduce acetylene / heteroatom mixed gas, and obtain a multi-atom doped silicon-carbon composite negative electrode material after the reaction is completed. The heteroatom gas in the acetylene / heteroatom mixed gas is phosphine, the flow rate of the acetylene / heteroatom mixed gas is 500SCM, and the introduction time of the acetylene / heteroatom mixed gas is 60min. The volume ratio is acetylene:phosphine = 10:5, and the heating temperature of the rotary kiln is 500℃.

[0073] Comparative Example 1: Different from Example 1, copper chloride powder is not added in step S1, and the rest is the same as Example 1.

[0074] Comparative Example 2: Different from Example 1, no nitrogen source and lithium source gas are introduced in step S3, and the rest is the same as Example 1.

[0075] Experiment 1, SEM test: Figure 2 This is a SEM image of the multi-atom doped silicon-carbon composite negative electrode material prepared in Example 1. It can be seen from the image that the material has a granular structure with a uniform size distribution and a particle size between 5-10 µm.

[0076] Experiment 2: Physical and chemical performance test: The specific surface area of ​​each multi-atom doped silicon-carbon composite negative electrode material obtained in Examples 1-3 and Comparative Examples 1-2 was tested in accordance with the method in the national standard GB / T 38823-2020 "Silicon Carbon"; and the powder resistivity of each multi-atom doped silicon-carbon composite negative electrode material was tested using a four-probe tester. At the same time, the gas production of each multi-atom doped silicon-carbon composite negative electrode material was also tested (100g of powder was added to deionized water, and its gas production was tested after standing at a temperature of 45°C for 48 hours).

[0077] Experiment 3, button battery test: The polyatom-doped silicon-carbon composite negative electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 were used as active materials for negative electrode plates of batteries and were respectively prepared and assembled into button batteries; wherein the specific preparation process of each button battery is as follows: Preparation of battery negative electrode sheets: Add a binder, a conductive agent and a solvent to each polyatom-doped silicon-carbon composite negative electrode material (as an active material of the battery negative electrode sheet) corresponding to Examples 1-3 and Comparative Examples 1-2, stir to make a slurry, apply it on a copper foil, and dry and roll to obtain each battery negative electrode sheet; wherein the binder is LA132 binder, the conductive agent is SP (conductive carbon black), and the solvent is NMP, and the ratio is: polyatom-doped silicon-carbon composite negative electrode material: SP: LA132: NMP = 95g: 1g: 4g: 220mL; Preparation of button cells: LiPF6 solution was used as the electrolyte, wherein the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a weight ratio of 1:1; a metal lithium sheet was used as the counter electrode, and a polypropylene (PP) film was used as the diaphragm. The simulated battery was assembled in an argon-filled glove box, and the electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester. The test conditions were: the charge and discharge voltage range was 0.005 V to 2.0 V, and the charge and discharge rate was 0.1 C. The first discharge specific capacity and the first efficiency were calculated, and the charged DCR (50% SOC) of the button cell was tested.

[0078] The button cells made using the multi-atom doped silicon-carbon composite negative electrode materials provided in Examples 1-3 of the present application are significantly better than those in Comparative Examples 1-2 in terms of first discharge specific capacity, first efficiency and powder resistivity. The reason is that in the example materials, the pore volume of the material is increased by pore formation through copper chloride, which increases the amount of lithium that the material can accommodate, thereby increasing the specific capacity; at the same time, metallic lithium and heteroatoms are doped to reduce the powder resistance of the material.

[0079] Experiment 4, soft pack battery test: The polyatom-doped silicon-carbon composite negative electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 were doped with 90% artificial graphite as the negative electrode material (i.e., the negative electrode plate), and the ternary material LiNi1 / 3Co1 / 3Mn1 / 3O2 was used as the positive electrode material, the electrolyte and the diaphragm were assembled into a 5Ah soft-pack battery; wherein the diaphragm of the soft-pack battery was Celegard 2400, the electrolyte was LiPF6 solution, wherein the solvent of the LiPF6 solution was a mixed solution of EC and DEC in a volume ratio of 1:1, and the concentration of LiPF6 was 1.1 mol / L; the following performance tests were carried out on each soft-pack battery: a. Liquid absorption capacity test: Use a 1mL burette and absorb 1mL of electrolyte, add a drop of electrolyte on the surface of each negative electrode, and time it until the electrolyte is completely absorbed, and record the time t; the test results are shown in Table 2.

[0080] b. Electrode sheet surface resistance: The electrode sheet surface resistance is tested using a surface resistance tester; the test results are shown in Table 2 below.

[0081] Table 2: It can be seen from Table 2 above that the liquid absorption capacity and surface resistance of the multi-atom doped silicon-carbon composite negative electrode materials provided in Examples 1-3 of the present application are significantly higher than those in Comparative Examples 1-2. The reason is that the example materials have a large specific surface area and a low powder resistivity, thereby reducing the surface resistance of the electrode and increasing the liquid absorption speed of the material.

[0082] c. Rate and cycle performance: The soft-pack batteries were subjected to cycle performance tests and rate tests. The test conditions for the cycle performance test were as follows: the charge and discharge voltage range was 2.5-4.2V, the temperature was 25±3.0°C, the charge and discharge rate was 1.0C / 1.0C, and the number of cycles was 500; the test conditions for the rate test were as follows: each soft-pack battery was charged to 4.2V at a constant current of 2C, and then charged to 100% SOC at a constant voltage at a rate of 0.1C, and the 2C constant current ratio was calculated to be 2C constant current capacity / (2C constant current capacity+0.1C constant voltage capacity).

[0083] The test results are shown in Table 3 below.

[0084] Table 3: It can be seen from Table 3 above that the soft-pack lithium-ion batteries prepared by using the multi-atom doped silicon-carbon composite negative electrode materials provided by Examples 1-3 of the present application perform significantly better than Comparative Examples 1-2 in rate performance and cycle performance. The reason is that the example materials have low electrode sheet surface resistance, which improves the fast charging performance of the material; and the implementation of the lithium material contains copper chloride for reduction to generate metallic copper and a porous structure, which improves the electronic conductivity of the material and its porous structure reduces expansion, thereby improving the cycle performance. In addition, the example deposits metallic lithium to provide sufficient lithium ions during the charge and discharge process, thereby improving the cycle performance.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a multi-atom doped silicon-carbon composite negative electrode material, characterized in that the steps include: S1. Transferring a biomass carbon-based precursor and a copper metal dopant to a tube furnace, and performing a carbonization reaction to obtain porous carbon, wherein the mass ratio of the biomass carbon-based precursor to the copper metal dopant is 500:10-30, the biomass carbon-based precursor comprises at least one of coconut shell, rice shell, fruit shell, and sawdust, and the copper metal dopant comprises at least one of copper chloride, copper nitrate, and copper sulfate; S2, transferring the porous carbon to a fluidized bed reactor, introducing an organic carbon source / hydrogen mixed gas to carry out a reduction reaction, and obtaining copper-doped porous carbon; S3, transferring the copper-doped porous carbon to a vacuum furnace, introducing nitrogen source gas, lithium source gas, and silicon source / carbon source mixed gas in sequence for multiple staged reactions to obtain a silicon-carbon precursor; S4, transferring the silicon-carbon precursor to a rotary furnace, heating it and introducing acetylene / heteroatom mixed gas, and obtaining a multi-atom doped silicon-carbon composite negative electrode material after cooling.

2. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 1, characterized in that: The step S1 comprises: S1.1, the biomass carbon-based precursor and the copper metal dopant are mixed evenly and then transferred to a tube furnace for the first heating, wherein the temperature of the first heating is 700-900° C. and the time of the first heating is 1-6 hours; S1.

2. After the first heating is completed, a second heating is performed and an activated gas is introduced to obtain porous carbon, wherein the temperature of the second heating is 1000-1200°C, the time of the second heating is 1-3h, the activated gas includes at least one of water vapor, carbon dioxide, and hydrogen, and the flow rate of the activated gas is 100-500ml / min.

3. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 1, characterized in that: In the step S2, the pressure condition of the reduction reaction is 0.1-0.5 MPa, the temperature of the reduction reaction is 700-900° C., and the time of the reduction reaction is 1-10 h.

4. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 1, characterized in that: The step S3 comprises: S3.1, transferring the copper-doped porous carbon to a vacuum furnace, adjusting the gas pressure to 0.1-0.5 MPa, performing the first stage heating and introducing a nitrogen source gas, wherein the nitrogen source gas includes at least one of ammonia, nitrogen, and nitric oxide, the flow rate of the nitrogen source gas is 10-50 SCCM, the introduction time of the nitrogen source gas is 0.5-3 h, and the temperature of the first stage heating is 600-900 ° C; S3.2, after stopping the introduction of the nitrogen source gas, performing the second stage heating and introducing the lithium source gas, wherein the temperature of the second stage heating is 1000-1400°C, the lithium source gas comprises at least one of lithium hydride and lithium vinyl, the flow rate of the lithium source gas is 100-500 SCCM, and the introduction time of the lithium source gas is 0.5-3h; S3.

3. After stopping the introduction of the lithium source gas, the third stage of heating is carried out and a silicon source / carbon source mixed gas is introduced to obtain a silicon-carbon precursor, wherein the temperature of the third stage heating is 400-600°C, the silicon source gas in the silicon source / carbon source mixed gas includes at least one of monosilane, disilane, dichlorosilane, and trichlorosilane, the carbon source gas in the silicon source / carbon source mixed gas includes at least one of ethylene, acetylene, propane, cyclohexane, methane, and benzene, the flow rate of the silicon source / carbon source mixed gas is 100-500 SCCM, and the introduction time of the silicon source / carbon source mixed gas is 1-10 hours.

5. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 4, characterized in that: In the step S3.3, the volume ratio of the silicon source gas to the carbon source gas in the silicon source / carbon source mixed gas is 10:1-5.

6. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 1, characterized in that: In step S4, the heteroatom gas in the acetylene / heteroatom mixed gas includes at least one of hydrogen sulfide, ammonia, phosphine, and tetrahydrogen dinitrogen, the flow rate of the acetylene / heteroatom mixed gas is 100~500SCM, and the introduction time of the acetylene / heteroatom mixed gas is 1~10h.

7. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 6, characterized in that: The step S4 comprises: S4.1, transferring the silicon-carbon precursor to a rotary furnace, first heating it to a first temperature and introducing acetylene / heteroatom mixed gas, wherein the first temperature is 200-300° C.; S4.

2. Maintain the preset heating rate to heat up to the second temperature, and at the same time adjust the rotation speed of the rotary kiln and the flow rate of the acetylene / heteroatom mixed gas. After the acetylene / heteroatom mixed gas is introduced, it is cooled to obtain a multi-atom doped silicon-carbon composite negative electrode material, wherein the rotation speed is positively correlated with the flow rate of the acetylene / heteroatom mixed gas, wherein the preset heating rate is 5~80℃ / h, and the second temperature is 400~500℃.

8. The method for preparing the multi-atom doped silicon-carbon composite negative electrode material according to claim 1, characterized in that: The multi-atom doped silicon-carbon composite negative electrode material is applied to lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method and application of porous silicon oxide / carbon composite negative electrode material

    CN110112376A

  • Preparation method of nitrogen-phosphorus doped porous carbon coated manganese dioxide negative electrode material

    CN112467120A

  • Preparation method of copper-doped porous carbon-silicon-oxygen composite material, composite material and application

    CN115676837A

  • Copper-doped porous carbon material, silicon-carbon composite material and application thereof

    CN119008894A

  • Decomposition of silicon-containing precursors on porous scaffold materials

    US20200020935A1